(untitled) (Arghand Journal of Social Sciences, 2026)
The liberal international order contributed to rising global instability in economic, security, and institutional spheres. Using an analytical-descriptive approach, a qualitative research design was employed to test the proposed conceptual framework. The research draws on recent scholarly debates, policy analyses, and empirical data on trade measures, alliances, security agreements, and changes in foreign aid to understand better how American global engagement has evolved and what that shift means for the wider world. The findings suggest that renewed economic protectionism, expansive tariff regimes, withdrawal from multilateral agreements, reduced support for international institutions, and sharp nationalist rhetoric have collectively disrupted established patterns of global cooperation. These developments have strained long-standing alliances, intensified U.S.- China rivalry, unsettled global trade systems, weakened arms-control arrangements, and reduced support for humanitarian and climate initiatives. The study underscores the importance of rebuilding trust, revitalising multilateral cooperation, and strengthening international institutions to prevent deeper systemic fragmentation. By examining economic, institutional, security, and ideological dimensions together, this research offers a comprehensive and accessible account of how Trump’s second-term policies have contributed to a more fragmented and uncertain global order.